2017
DOI: 10.1101/173377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parasympathetic and Sympathetic Activity Are Associated with Individual Differences in Neural Indices of Selective Attention in Adults

Abstract: Multiple theoretical frameworks posit that interactions between the autonomic nervous system and higher-order neural networks are crucial for cognitive regulation. However, few studies have directly examined the relationship between measures of autonomic physiology and brain activity during cognitive tasks, and fewer studies have examined both the parasympathetic and sympathetic autonomic branches when doing so. Here, 93 adults completed an event-related potential (ERP) auditory selective attention task concur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 79 publications
(103 reference statements)
4
13
0
Order By: Relevance
“…Significant correlations between the HF‐HRV block effect and the N1 block effect were found. This is in line with previous studies in which HF‐HRV has been shown to be related to arousal level (Giuliano et al, ; ). HRV provides valuable information about the capacity of the organism to effectively function in a complex environment (Thayer et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Significant correlations between the HF‐HRV block effect and the N1 block effect were found. This is in line with previous studies in which HF‐HRV has been shown to be related to arousal level (Giuliano et al, ; ). HRV provides valuable information about the capacity of the organism to effectively function in a complex environment (Thayer et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Selective attention allows the efficient coordination of the organism for goal‐directed behavior in a changing environment with potential threat (Lavie, Hirst, De Fockert, & Viding, ; Thayer & Lane, ). Previous studies have shown that the target central area of stress (e.g., SN) and the stress‐related peripheral response are associated with selective attention processing (Giuliano et al, ; Sara & Bouret, ; Thayer & Lane, ). Therefore, selective attention processing might be influenced by stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies support this conclusion (Allen, Jennings, Gianaros, Thayer, & Manuck, ; Jennings, Sheu, Kuan, Manuck, & Gianaros, ; Sakaki et al, ). Resting vmHRV is also associated with evoked potential indicators of selective attention (Giuliano et al, ), and brain stimulation studies support associations with prefrontal activity (Makovac, Thayer, & Ottaviani, ).…”
Section: Empirical Findingsmentioning
confidence: 98%
“…Pre‐ejection period (PEP) is a hemodynamic measure of myocardial contractility that is widely used by psychophysiologists as a valid index of sympathetic beta‐adrenergic influences upon the heart (Bagley & El‐Sheikh, ; Cacioppo et al, ; Gatzke‐Kopp & Ram, ; Giuliano et al, ; Schächinger, Weinbacher, Kiss, Ritz, & Langewitz, ; Sherwood, Allen, Obrist, & Langer, ).…”
Section: Introductionmentioning
confidence: 99%